Mining Business License Area For Religious Community Organizations In The Perspective Of The Welfare State - Zakiyatun Nufus; Fendi Setyawan; Galuh Puspaningrum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The purpose of this study is to analyze the Special Mining Business Permit Area for Religious Community Organizations in the Perspective of the Welfare State (Walfare State). This study uses normative legal research methods using a legislative approach and a conceptual approach. This study uses the theory of legal certainty, the theory of justice, and the theory of the welfare state as analytical knives in analyzing these problems. The results of the study show that the legal transformation in policies related to Article 83A PP No. 25/2024 is formally irrelevant to the rules above, namely in Law Number 4 of 2009 and Law Number 3 of 2020. However, the rules are still valid and can be implemented responsibly and professionally based on the analysis of legislation and theoretical analysis carried out by researchers, decisions made by government officials have binding force on all members of society, and have a public function, in the sense of performing public services.